Lesi Medulla Spinalis - Rahmat Juli Setiadi; Herlina Herlina (Jurnal Kesehatan Amanah, 2023)
Spinal cord injury is one of the main causes of neurological disability due to trauma. The most common cause of spinal cord trauma is due to traffic accidents, etc. Spinal cord trauma itself is classified into complete spinal cord trauma and incomplete spinal cord trauma. While the most common symptoms of spinal cord trauma are acute pain in the back of the neck, paraplegia, total motor sensory paralysis, loss of bladder control (urine retention, bladder distention), decreased sweating and vasomotor tone, decreased respiratory function, respiratory failure. Treatment of spinal cord injuries is primarily aimed at improving and maintaining sensory and motor function. Operative therapy is not recommended unless the patient has an indication for surgery. Incomplete spinal cord injuries tend to have a better prognosis than complete spinal cord injuries.